Subsurface drainage at irrigation project Maniçoba: design criteria and performance - Suguino, Herminio H.; Cordeiro, Gilberto G.; Júnior, Walter Caldas; Valdivieso, Carlos R. (Pesquisa Agropecuaria Brasileira, 2014)
This study was carried out on a parallel subsurface pipe drainage system (1.5 ha) installed for this purpose in a Class 3 soil plot of Irrigation Project Maniçoba, BA, Brazil, in order to determine the applicability of drain spacing equations, check some soil hydrological parameters and adjust design criteria. Drain spacing and combination of envelope materials were the variables considered. The drains spacing (L.) was calculated based on parameters determined in situ and using equations of Hooghoudt and Glover-Dumm. Twice the calculated spacing was considered for variation of this parameter. Depth of water table and rain discharges as response to recharge (surface irrigation or rainfall) were registered for drains spaced L = 15 m and L = 30 m also monitoring soil moisture. Eventually, chemical composition and sediments content of drainage water was determined in the laboratory. Results of this study show that the L = 30 m spacing kept better soil moisture regime in the profile. The peak instantaneous drain discharge was 8 to 10 mm/day falling to 4 mm/day or less three days after recharge took place. The mean water table depth during the study was 0.6 m to 1.0 m below ground surface for L = 30 m and 1.2 m to 1.5 m for L = 15 m. Contribution of soil layers below drain level to underground flow was found negligible. Auger hole method proved a very precise one for the determination of hydraulic conductivity in situ. Hooghoudt equation overestimated the spacing in 24% and Glover-Dumm equation underestimated it in 30%. Drainable porosity values found were 7.8% and 24% and drainage intensity factor determined varied from 0.15 to 0.21.
Keywords: hydrological parameters; drainage; envelope materials; variations